1980
DOI: 10.1902/jop.1980.51.4.228
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Repetition and Reinforcement in Improving Oral Hygiene Performance

Abstract: The purpose of this study was to assess the value of including repetition and reinforcement in a dental health education program for school children. Sixty-one pupils, 11 to 13 years of age, were divided into three groups according to room assignments. Group I (control) received no oral hygiene lectures or instructions until the conclusion of the experiment. Group 2 (nonreinforced) received one lecture and a toothbrushing lesson, but no repetition or reinforcement. Group 3 (reinforced) received the same progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
9

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 33 publications
1
31
0
9
Order By: Relevance
“…Addressing these barriers is within our reach and we have a moral duty to do so. It has been suggested by authors that the role of those directly responsible for conducting dental health programs is important in bringing about the desired results . If support staff had conducted the present investigation, such as staff auxiliaries, elementary teachers, or peers, the results could have been less positive.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Addressing these barriers is within our reach and we have a moral duty to do so. It has been suggested by authors that the role of those directly responsible for conducting dental health programs is important in bringing about the desired results . If support staff had conducted the present investigation, such as staff auxiliaries, elementary teachers, or peers, the results could have been less positive.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, since regular reinforcement was done, it could have resulted in the better uptake of knowledge. Several other investigations have confirmed that multiple reinforcements along with one‐on‐one oral hygiene instructional program lasting for at least 3 months can maintain improved oral hygiene in children for the duration of the program . The fact that all of the participants were aware that they would be participating in an oral hygiene instructional program prior to the collection of baseline values may have positively influenced the results, however, none of the students knew in advance exactly which day the investigator would be coming to the school or exactly what activities would occur, and who all will be examined that day.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reduction in OHI-S was observed at the end of 12 months. Repeated sessions would probably have brought a better impact in oral hygiene, as has been emphasized elsewhere [18,19]. Emphasizing some immediate gains from good oral hygiene [18] (such as fresh breath; clean, Yatish Kumar Sanadhya et al, Effectiveness of oral health education among fishermen's children in India white teeth; and attractive appearance) were key aspects for motivating these students to learn and maintain good oral health.…”
Section: Discussionmentioning
confidence: 98%
“…It must be remembered that the subjects were only instructed in flossing prior to the study and no further instruction was given once the experiment had commenced. Lightner et al (1971) and Elmer et al (1980) have shown that the more frequently subjects are instructed in a certain plaque control procedure, the lower will be their plaque scores. In practice, it is important to show patients which areas of the mouth are being imperfectly cleaned and by doing so, they will probably pay more attention to these areas while exercising their cleaning efforts.…”
Section: Discussionmentioning
confidence: 99%